Correlation of Zakat and Tax in the Framework of Sharia Economic Law - Ariyadi, Ariyadi (el Buhuth: Borneo Journal of Islamic Studies, 2024)
Talking about welfare issues, of course, one of the instruments that can be drawn to solve it through zakat and taxes, in making policies of course we will be faced with whether zakat is the same, or even the opposite is contradictory and can be taken both for the word category of artistic benefit is trying to elaborate whether it is an understanding of Islamic economic law? The tax system according to Islam is the tax system applied during the reign of the Prophet and the government of Khulafarusshidin. At that time, the state budget was still very simple and not as complicated as the modern budget system. The state uses the principle of a balanced budget (balance budjet). State revenues can be very different from year to year, even from day to day.and so is zakat.